2016
DOI: 10.5301/ejo.5000830
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Cationic Emulsion in the Treatment of Moderate to Severe Dry Eye Disease: A Randomized Controlled Study

Abstract: CE was similar to HS with regards to safety and efficacy for objective signs but was superior to HS in improving DED symptoms in patients with moderate to severe DED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 37 publications
(43 reference statements)
3
52
0
3
Order By: Relevance
“…This fundamental surface chemistry and in silico molecular dynamics simulations research on CEs and their molecular components (polar lipids and hydrophilic surface-active excipients) explain from a mechanistic physicochemical point of view the improvement in TF break-up time observed in clinical trials, for both the CE ATs 10,34 and CE drug products. 11,35 In addition, a comparison of CE versus a polyvinyl alcohol and povidone-based lubricant demonstrated that a statistically significant improvement in tear break-up time was observed on day 28 (+2.0 vs. +0.5 s; P = 0.0349) in MGD patients treated with the CE, hence confirming that the CE may act on the TF stability.…”
Section: Improved Tf Stability With the Cesmentioning
confidence: 76%
See 2 more Smart Citations
“…This fundamental surface chemistry and in silico molecular dynamics simulations research on CEs and their molecular components (polar lipids and hydrophilic surface-active excipients) explain from a mechanistic physicochemical point of view the improvement in TF break-up time observed in clinical trials, for both the CE ATs 10,34 and CE drug products. 11,35 In addition, a comparison of CE versus a polyvinyl alcohol and povidone-based lubricant demonstrated that a statistically significant improvement in tear break-up time was observed on day 28 (+2.0 vs. +0.5 s; P = 0.0349) in MGD patients treated with the CE, hence confirming that the CE may act on the TF stability.…”
Section: Improved Tf Stability With the Cesmentioning
confidence: 76%
“…Although it is the most hydrophobic subcomponent of the benzalkonium chloride (BAK) mixture-which explains its improved safety profile when formulated in emulsion 8,9,58-61 versus the benzyl alkyl quaternary ammoniums chloride with shorter aliphatic chains (12 or 14 carbons) 8,9 -it was not anticipated that CKC, through its modulation of PKCa, could be even partly responsible for the good clinical performance of the CEs. 10,11,35 Indeed, Pflugfelder and collaborators demonstrated in a PKCa knock-out mouse the benefits that PKCa ''inhibition'' has on corneal inflammation and its healing process. 62 When formulated in CEs, CKC does not harbor any of the detrimental side effects of the shorter BAK quaternary ammonium compounds, but instead offers the benefits of modulating PKCa for the management of inflammation and the improvement of wound-healing processes in DE patients in addition to mechanically stabilizing the TFLL.…”
Section: Reduced Hyperosmolarity and Its Associated Cellular Stress Wmentioning
confidence: 99%
See 1 more Smart Citation
“… 84 In another clinical trial of Cationorm and Vismed ® (TRB Chemedica) in patients with moderate-to-severe dry eye, although both eye drops showed similar safety profiles and efficacy in terms of improvements in objective signs of dry eye, Cationorm was superior in improving the global symptoms score of ocular discomfort. 85 …”
Section: Lipid-based Therapiesmentioning
confidence: 99%
“…Cationorm ® (CN) cationic nanoemulsion (see Section 4.1 for CN composition) was shown to enhance tear film stability at the ocular surface possibly via effect on tear film lipid layer (TFLL) [ 23 , 24 ]. Thus the impact of CN on human meibum and TFLL in vitro and in vivo have to be studied in detail.…”
Section: Introductionmentioning
confidence: 99%